Role of the Neutrophil-to-Lymphocyte Ratio at the Time of Arrival at the Emergency Room as a Predictor of Rhabdomyolysis in Severe Trauma Patients - Jin Chul Bae; Kyung Hoon Sun; Yong Jin Park (Journal of Trauma and Injury)
Purpose In patients with trauma, rhabdomyolysis (RM) can lead to fatal complications resulting from muscle damage. Thus, RM must be immediately diagnosed and treated to prevent complications. Creatine kinase (CK) is the most sensitive marker for diagnosing RM. However, relying on CK tests may result in delayed treatment, as it takes approximately 1 hour to obtain CK blood test results. Hence, this study investigated whether the neutrophil-to-lymphocyte ratio (NLR) could predict RM at an earlier time point in patients with trauma, since NLR results can be obtained within 10 minutes. Methods This retrospective study included 130 patients with severe trauma who were admitted to the emergency room of a tertiary institution between January 2017 and April 2020. RM was defined as a CK level ≥1,000 U/L at the time of arrival. Patients with severe trauma were categorized into non-RM and RM groups, and their characteristics and blood test results were analyzed. Statistical analysis was performed using SPSS version 26.0 for Windows. Results Of the 130 patients with severe trauma, 50 presented with RM. In the multivariate analysis, the NLR (odds ratio [OR], 1.252; 95% confidence interval [CI], 1.130–1.386), pH level (OR, 0.006; 95% CI, 0.000–0.198), presence of acute kidney injury (OR, 3.009; 95% CI, 1.140–7.941), and extremity Abbreviated Injury Scale score (OR, 1.819; 95% CI, 1.111–2.980) significantly differed between the non-RM and RM groups. A receiver operating characteristic analysis revealed that a cut-off NLR value of 3.64 was the best for predicting RM. Conclusions In patients with trauma, the NLR at the time of arrival at the hospital is a useful biochemical marker for predicting RM.